Novel albendazole formulations given during the intestinal phase of Trichinella spiralis infection reduce effectively parasitic muscle burden in mice - García, Agustina (2013)
Trichinellosis is a zoonotic disease affecting people all over the world, for which there is no speedy and reliable treatment. Albendazole (ABZ), an inexpensive benzimidazole used in oral chemotherapy against helminthic diseases, has a broad spectrum activity and iswell tolerated. However, the low absorption and variable bioavailability of the drug due to its low aqueous solubility are serious disadvantages for a successful therapy. In this study, we evaluated the in vivo antiparasitic activity of three novel solid microencapsulated formulations, designed to improve ABZ dissolution rate, in amurinemodel of trichinellosis. Both ABZ and the microparticulate formulations were administered during the intestinal phase of the parasite cycle, on days 5 and 6 post-infection. This protocol significantly decreased muscle larval burden measured in the parenteral phase, on day 30 post-infection, when compared with the untreated control. Moreover, two of the three microencapsulated formulations both strongly and consistently reduced worm burden.